Characterization of fabricated optical fiber for food irradiation dosimetry - Mohd Noor, Noramaliza; A. J., Maryam; S., Hassan; Wan Abdullah, Wan Saffiey; Tamchek, Nizam; M., Faizal; David, A. B.; Abdull Razis, Ahmad Faizal (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Food irradiation is a process carried out in order to improve hygienic quality and germination control, retarding sprouting, also enhancing physical attributes of the food product. In order to provide for food safety, radiation dosimetry in irradiated foods is required. In present studies use is made of germanium doped (Ge-doped) optical fibres of various form and dimensions. The fibres are irradiated using a gamma source irradiator (Gamma Cell 220 Excel), with doses from 1 kGy up to 10 kGy. For the particular Ge-doped optical fibres, investigation has been made of linearity with dose, reproducibility, and fading, intercomparisons being made. The fibres all exhibit TL yields that are linear with dose from 1 kGy up to 10 kGy, exceeding the dose range of all commercial high dose dosimeters used in the food irradiation industry. In respect of the flat fibre dosimeters, the mean reproducibility was found to be within 0.53% to 4.96%, also offering low signal loss (fading), within 13.41% (for fibres of cross-sectional dimensions 60 x 180 μm) to 20.12% (for fibres of cross-sectional dimensions 200 x 750μm), after 22 days of storage.